Who is in private prisons? Demographic profiles of prisoners and workers in American private prisons - Burkhardt, Brett C. (International journal of law, crime and justice, 2017)
Who is in private prisons? This seemingly straightforward question has received surprisingly little attention in the United States. This paper analyzes national prison data to provide demographic profiles of prisoners and workers in private prisons in the United States and to compare them to prisoners and workers in state and federal prisons. It summarizes data on jurisdiction, sentence length, race, and citizenship of prisoners, as well as the race and gender of correctional officers. Results reveal differences between private and public prisons with respect to both prisoners and workers. Specifically, private prisons detain inmate populations that are disproportionately non-white, under federal jurisdiction, and serving short sentences; and they employ officers that are disproportionately female and black or Hispanic. These results depict the private prison sector as distinct from its public counterpart—both in terms of prisoner and staff composition. A discussion considers the implications of these findings for equity in punishment.